Effect of Maternal Age, Parity and Placental Weight on Birth Weight in Otanaha Hospital, Gorontalo City - Puspita Sukmawaty Rasyid; Endah Yulianingsih (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Birth weight is an indicator of fetal growth whether healthy or experiencing problems during the womb. Low birth weight (LBW) has an effect on high infant morbidity and mortality rates. Data obtained from the delivery room of the Otanaha Hospital showed the prevalence of LBW births in 2018 was 1.83% and had increased in 2019 to 3.25%. The factors that influence birth weight included the age of the mother, parity and weight of the placenta. The research objective was to determine the effect of maternal age, parity and placental weight on birth weight at the Otanaha Hospital, Gorontalo City. This research type was analytic observation with cross sectional study approach. The sampling technique used was accidental sampling technique with a total of 60 respondents.The data analysis used was the Chi-Square statistical test. The results of the univariate analysis of 60 respondents showed that the age group without risk was 42 (70.0%), parity without risk was 41 (68.3%), normal placental weight was 31 (51.7%) and normal birth weight was 46 (76.7%). Bivariate analysis showed the variable maternal age and parity with p-value 0.065 and 0.526 (p> 0.05) and placental weight variable with p-value 0.000 (p <0.05). The conclusion of the study showed that maternal age and parity had no effect on birth weight, while placental weight had an effect on birth weight of infants at Otanaha Hospital, Gorontalo City.